The Myth of Sovereignty in the Era of Hyper-Globalisation: Western Fears, Postcolonial Realities (Groundings Undergraduate, 2024)
Globalisation has made it necessary to review modernity’s paradigms. One such paradigm that may no longer be an accurate descriptor (if it ever was) of international society is that of the sovereign nation-state.Through an exploration of both the western nation-state and the space collectively referred to as ‘postcolony’, two different experiences of globalisation are exhibited, each with different power manifestations. For the former, globalisation has challenged both internal and external legitimacy, which as in turn led to perceptions of a loss of sovereignty. However, the loss of sovereignty does not imply the loss of power; sovereign power has morphed into biopower, with power remaining within that space. In contrast, the postcolony’s historical relationship with sovereignty is one of negation- the denial of it. Globalisation thus threatens not the specific manifestation of power in sovereignty, but rather the continued subordination to western sovereignty. This has occurred due to a continuation of the ‘state of exception’ and socioeconomic hegemony.The piece does not, however, claim to be a definitive analysis of power, sovereign or otherwise, under globalisation. Such an inquiry would be a much greater project that went beyond the two broad categories west/postcolony, looking at specific national contexts: ‘realities’ rather than ‘reality’, accounting for the heterogeneity of both the forms and experiences of colonialism. It is a map of the terrain, and like any map is pitched at the level of generalisation.
Keywords: Sovereignty; Globalisation; Postcolony; Nation-state; Colonialism; Biopower